THE PERSPECTIVE OF PRIMARY SCHOOL TEACHERS IN TEACHING ENGLISH - Agustinus Triwinanta; Markus Budiraharjo (IKIP Siliwangi, 2022)
At this time the role of English is very important in all areas of human life, especially in the field of education. The education policy to introduce English at primary school age has been implemented. Many schools have included English as a local content subject in the school curriculum. And in learning the teacher uses English as the language of instruction